2022
DOI: 10.1039/d2ee00264g
|View full text |Cite
|
Sign up to set email alerts
|

Key roles of surface Fe sites and Sr vacancies in the perovskite for an efficient oxygen evolution reactionvialattice oxygen oxidation

Abstract: Oxygen evolution reaction participated by lattice oxygen oxidation (LOER) on the perovskite catalyst has attracted great interest recently because of its low reaction energy barrier. However, as the surface structure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(66 citation statements)
references
References 55 publications
1
65
0
Order By: Relevance
“…These results suggest that the improved catalytic performance can be attributed to the synergistic effect of Co doping and oxygen vacancies. Notably, the OER activity of the as-prepared C-NP-NCOH electrode is comparable [43][44][45][46][47][48][49][50] or superior to those of reported OER electrocatalysts (Fig. S3a †).…”
Section: Electrocatalytic Activitymentioning
confidence: 85%
“…These results suggest that the improved catalytic performance can be attributed to the synergistic effect of Co doping and oxygen vacancies. Notably, the OER activity of the as-prepared C-NP-NCOH electrode is comparable [43][44][45][46][47][48][49][50] or superior to those of reported OER electrocatalysts (Fig. S3a †).…”
Section: Electrocatalytic Activitymentioning
confidence: 85%
“…The difference from the AEM pathway is that the deprotonated *O directly couples with the activated lattice oxygen to form *OO species rather than waiting for nucleophilic attack of H 2 O/OH – from the electrolyte. The representative case is the La 1– x Sr x CoO 3−δ perovskite oxides with a high Sr 2+ component, together with the related derivatives. ,, DFT calculations underlined that the direct O–O coupling of *O with lattice oxygen was thermodynamically spontaneous (i.e., Δ G < 0) in SrCoO 3−δ (Figure a) . Similarly, in a proposed Zn x Co 1– x OOH oxyhydroxide with the Zn 2+ -induced O NB state, integrating *OH deprotonation with hole-doped lattice oxygen in one step (Step 1 in the SMSM pathway; see Figure b) became energetically favorable as compared to conventional *OH-to-*O in the AEM pathway alongside the Zn 2+ increment as well as the ligand hole level in the O NB state .…”
Section: Roles Of Lattice Oxygen Activation On the Oermentioning
confidence: 97%
“…In particular, iron group transition metals such as Fe-, Co-, and Ni and their derivatives are extensively used as effective electrocatalysts for OER in alkaline medium due to their suitable electronic configuration, physiochemical properties, and mechanical properties. , Nowadays, 3d transition-metal-based layered double hydroxides are highly favored for the absorption of hydroxide and cleavage of oxygen by 3d–2p interactions between metals and hydroxide ions. LDH materials consist of M 2+ and M 3+ cations with intercalated anions, which are stacked between the layers of M 2+ /M 3+ ions . Particularly, pristine NiFe–LDHs and their analogues are currently gaining greater attention for OER electrocatalytic reactions in alkaline pH because of their high durability and compactness under operating conditions. Recently, Du et al reported the atmospheric corrosion-assisted NiFe–LDH with rich Fe defects for OER in 1 M KOH solution.…”
Section: Introductionmentioning
confidence: 99%
“…20,32−37 In particular, iron group transition metals such as Fe-, Co-, and Ni and their derivatives are extensively used as effective electrocatalysts for OER in alkaline medium due to their suitable electronic configuration, physiochemical properties, and mechanical properties. 38,39 Nowadays, 3d transition-metalbased layered double hydroxides are highly favored for the absorption of hydroxide and cleavage of oxygen by 3d−2p interactions between metals and hydroxide ions. 40−43 LDH materials consist of M 2+ and M 3+ cations with intercalated anions, which are stacked between the layers of M 2+ /M 3+ ions.…”
Section: ■ Introductionmentioning
confidence: 99%